Higher adherence with 3‐year entecavir treatment than lamivudine or telbivudine in treatment‐naïve Taiwanese patients with chronic hepatitis B. Issue 1 (January 2014) - Chien, Rong‐Nan; Peng, Cheng‐Yuan; Kao, Jia‐Horng; Hu, Tsung‐Hui; Lin, Chun‐Che; Hu, Chi‐Tan; Chen, Chi‐Yi; Hsieh, Tsai‐Yuan; Lin, Han‐Chieh; Chuang, Wan‐Long; ,
Abstract Background and Aims Oral nucleos(t)ide analogs (NAs) are effective in suppressing hepatitis B virus (HBV) replication in treatment naïve chronic hepatitis B (CHB) patients. However, little is known about the treatment modification and adherence on such patients with prolonged NA treatment. Methods In this multicenter observational study, a total of 600 NA‐naïve Taiwanese CHB patients aged 16 years and older were enrolled. The 600 patients were retrospectively identified by their NA treatment history from August 2008 to July 2009; this cohort was prospectively followed up over 3 years. During the 3‐year period, incidence of treatment modifications, reasons for modification, and rate of adherence were evaluated. Results Among the 583 evaluable patients, the initial NA treatment included entecavir (ETV) in 468 patients, telbivudine (LdT) in 67, and lamivudine (LVD) in 48. During the 3‐year treatment, 9.0% of ETV‐treated patients, 38.8% of LdT‐treated patients, and 54.2% of LVD‐treated patients had treatment modification. The main reasons for treatment modification were fulfilling stopping criteria in the ETV group (40.5%) and virological breakthrough in both the LdT (61.5%) and LVD (46.2%) groups. The proportion of patients with adherence rate (> 90%) at year 3 was 90.8% in the ETV group, 83.9% in the LdT group, and 83.9% in the LVD group. Conclusions Treatment‐naïve CHB patients with a 3‐year ETV treatment in Taiwan have the lower likelihood of treatment modification and better rate of adherence compared with those with LdT or LVD treatment.